Immunoglobulin-mediated immune dysregulation in recurrent pregnancy loss: mechanisms, biomarkers, and therapeutic perspectives - Kamala C; Pallavi Shekar; Umme Kulsum; Ananya Hegde; Lakshitha V Jayakrishna; Deepa Bhat; Meghana Hangala Shivakumaraswamy; Akila Prashant; Praveen Kumar K S (Immunologic Research, 2026)
Recurrent pregnancy loss (RPL) is a multifactorial reproductive disease that is typified by repeated pregnancy loss with immune dysregulation emerging as a critical contributing factor. Immunoglobulins are among the immune components that are instrumental in preserving tolerance between the mother and the fetus, regulating inflammatory responses, and supporting placental development. This review provides a comprehensive overview of the role of immunoglobulins in recurrent pregnancy loss, with particular emphasis on immune dysregulation, emerging biomarkers, and therapeutic implications. The immunoglobulin profiles, such as the changes in IgG subclasses and the presence of pathogenic autoantibodies, e.g. antiphospholipid and antinuclear antibodies, are highly correlated with unfavourable pregnancy outcomes. These changes, in a mechanistic manner, lead to poor trophoblast invasion, endothelial dysfunction, thrombosis and cytokine imbalance. Emerging evidence also highlights the contribution of regulatory B cells and the antibody-mediated immune network in maintaining pregnancy homeostasis. Immunoglobulin profiling has clinical potential as a diagnostic and prognostic methodology that can be used to stratify patients and provide customised therapy. Immunomodulatory therapies, especially intravenous immunoglobulin (IVIG), are potentially effective in a limited range of patient populations, but clinical response is variable. On the whole, this review demonstrates the role of immunoglobulin-mediated mechanisms in RPL and their future potential in enhancing precision medicine approaches to better diagnosis and management.

From flowers to pollinators: Dietary exposure of honey bees, bumble bees and solitary bees to trace elements across European fields - Maciej Durkalec; Agnieszka Nawrocka; Petru Jitaru; Marie-Pierre Chauzat; Marion Laurent; Matthias Albrecht; Cecilia Costa; Pilar De la Rúa; Alexandra-Maria Klein; Marika Mänd; Simon G. Potts; Maj Rundlöf; et al. (Journal of Hazardous Materials, 2026)

Enhancing Pharmacokinetics and Therapeutic Efficacy of Berberine via PEGylated Nanocarriers for Breast Cancer Treatment - Deepa Yadav; Bhupesh C. Semwal; Hitesh Kumar Dewangan; Mohamed Rahamathulla; Syeda Ayesha Farhana; Mohammed Muqtader Ahmed (Journal of Pharmaceutical Innovation, 2026)

Occurrence, Characterization, and Potential Ecological Risks of Microplastics in the Himalayan Riverine Systems - Deepa Kumari; Ramendra Pati Pandey; Ankur Rajpal; H. C. Sudheeksha; Smriti Arora (Bulletin of Environmental Contamination and Toxicology, 2026)

Advances in heavy metal removal from fruit juices: implications for food safety and quality control - G. Jeevarathinam; J. Deepa; Amarjit Singh Ningthoujam; Bedanta Rajbongshi; C. Nickhil; Shweta; Snigdha Chetia; Seema Ramniwas; S. Ganga Kishore; Davinder Pal Singh Oberoi; Sarvesh Rustagi; Syed Mohammed Basheeruddin Asdaq (Critical Reviews in Food Science and Nutrition, 2026)

Synthesis, Linear, and Nonlinear Optical Characteristics of Schiff Base N’,2-Bis((E)-4-Hydroxy-3-Methoxybenzylidene)Hydrazine-1-Carbohydrazide: Experimental and Computational Study - C. Deepa; E. David; A. G. Bharathi Dileepan; S. Jeyaram (Journal of Fluorescence, 2026)

A curcumin–resveratrol–carnosic acid complex mitigates brain–gut axis disruption in a rodent model of repeated mild traumatic brain injury - Mohind C Mohan; Anjana A S; Deepa Azhchath Vasu; Yadukrishnan M B; Aneesa P A; Tara Sudhadevi; Krishnakumar I M; Baby Chakrapani P S (Metabolic Brain Disease, 2026)

Oral delivery of an ustekinumab biosimilar with bioavailability comparable to subcutaneous administration in healthy human participants - Joshua T. Myers; Alyson Yamaguchi; Kyle Horlen; Leonard C. Fung; April Toledo Vo; Deepa Mohan; Mary Hoopes; Mir Imran; Jacques Van Dam; Ofer M. Gonen; Mir A. Hashim; Arvinder K. Dhalla; et al. (European Journal of Clinical Pharmacology, 2026)

Fluoroquinolone Resistant Enterobacteriaceae Isolated from Bagmati River and its Tributaries in Kathmandu, Nepal - Santosh Khanal; Joshna Thapa; Deepa Neupane; Suman SK; Sudeep K C; Tista Prasai Joshi; Dev Raj Joshi (Water, Air, & Soil Pollution, 2026)

A robust 1K-core marker set for wild germplasm management and targeted pre-breeding of rice: development and applications - Debashree Dalai; Dipti Ranjan Pani; Swayamsiddha Aswita Dhal; Motilal Behera; Tapan Kumar Mondal; Muhammad Azaharudheen TP; Joshitha Vijayan; Deepa Sarkar; Pallavi Ghose; Abhijeet Roy; Kutubuddin A Molla; Anilkumar C; et al. (Theoretical and Applied Genetics, 2026)

Exploring the role of MOFs in enhancing the durability of construction materials - Deepa Mundekkad; Anjali R. Mallya; William C. Cho (Arabian Journal of Geosciences, 2025)

The influence of climate modes on long-term sea level variability of the Indian ocean with special emphasis on the Southern Annular Mode: A study based on Indian ocean sea level reconstructions - J. S. Deepa; C. Gnanaseelan; K. V. Anusree (Theoretical and Applied Climatology, 2025)

Variation in the pollen diet of managed bee species across European agroecosystems - Clément Tourbez; Antoine Gekière; Irene Bottero; Marie-Pierre Chauzat; Elena Cini; Francesca Corvucci; Joachim R. de Miranda; Gennaro Di Prisco; Christophe Dominik; Francesca V. Grillenzoni; Simon Hodge; Tomasz Kiljanek; et al. (Agriculture, Ecosystems & Environment, 2025)

DFT and Z-scan Studies for the Determination of Nonlinear Optical Susceptibility and Second Order Hyperpolarizability of Ethidium Bromide Dye in Different Solvents - C. Deepa; A. G. Bharathi Dileepan; Rohith Ramasamy; Rajadurai Vijay Solomon; Natarajan Arumugam; Abdulrahman I. Almansour; Kasireddy Sudarshan; S. Jeyaram (Journal of Fluorescence, 2025)

Genetic diversity and population structure analysis in tamarind (Tamarindus indica L.) using SCoT and SRAP markers - C. Kanupriya; G. Karunakaran; Pritee Singh; R. Venugopalan; Deepa Samant; D. C. Lakshmana Reddy; K. Prakash (Genetic Resources and Crop Evolution, 2025)

On the skill of Indo-Pacific decadal sea level predictions and its connection with skilful AMO and PDO predictions - J. S. Deepa; C. Gnanaseelan (Climate Dynamics, 2024)

Development of dual stress-tolerant rice variety Jyothi with Saltol and Sub1 genes through marker-assisted backcross breeding - Deepa John; P. C. Rohini; K. S. Shylaraj (Cereal Research Communications, 2024)

Novel indices reveal that pollinator exposure to pesticides varies across biological compartments and crop surroundings - Marion LAURENT; Stéphanie BOUGEARD; Lucile CARADEC; Florence GHESTEM; Matthias ALBRECHT; Mark J.F. BROWN; Joachim DE MIRANDA; Reet KARISE; Jessica KNAPP; José SERRANO; Simon G. POTTS; Maj RUNDLÖF; et al. (Science of The Total Environment, 2024)

Integrating Multiscale Geospatial Analysis for Monitoring Crop Growth, Nutrient Distribution, and Hydrological Dynamics in Large-Scale Agricultural Systems - Olatunde D. Akanbi; Deepa C. Bhuvanagiri; Erika I. Barcelos; Arafath Nihar; Brian Gonzalez Hernandez; Jeffrey M. Yarus; Roger H. French (Journal of Geovisualization and Spatial Analysis, 2024)
Monitoring crop growth, soil conditions, and hydrological dynamics are imperative for sustainable agriculture and reduced environmental impacts. This interdisciplinary study integrates remote sensing, digital soil mapping, and hydrological data to elucidate intricate connections between these factors in the state of Ohio, USA. Advanced spatiotemporal analysis techniques were applied to key datasets, including the MODIS sensor satellite imagery, USDA crop data, soil datasets, Aster GDEM, and USGS stream gauge measurements. Vegetation indices derived from MODIS characterized crop-specific phenology and productivity patterns. Exploratory spatial data analysis show relationships of vegetation dynamics and soil properties, uncovering links between plant vigor, edaphic fertility, and nutrient distributions. Correlation analysis quantified these relationships and their seasonal evolution. Examination of stream gauge data revealed insights into spatiotemporal relationships of nutrient pollution and stream discharge. By synthesizing diverse geospatial data through cutting-edge data analytics, this work illuminated complex interactions between crop health, soil nutrients, and water quality in Ohio. The methodology and findings provide actionable perspectives to inform sustainable agricultural management and environmental policy. This study demonstrates the significant potential of open geospatial resources when integrated using a robust spatiotemporal framework. Integrating additional measurements and high-resolution data sources through advanced analytics and interactive visualizations could strengthen these insights.

Phenotypic diversity in Tamarindus indica L. sourced from different provenances in India - C. Kanupriya; G. Karunakaran; Pritee Singh; R. Venugopalan; Deepa Samant; K. Prakash (Agroforestry Systems, 2024)

Celiac Disease: An Academy of Nutrition and Dietetics Evidence-Based Nutrition Practice Guideline - Joann M. McDermid; M. Angie Almond; Kristen M. Roberts; Emily M. Germer; Marilyn G. Geller; Theresa A. Taylor; Rachel C. Sinley; Deepa Handu (Journal of the Academy of Nutrition and Dietetics, 2023)

Sustaining Rice-Wheat System Through Integrated Nutrient Management via FYM or Sesbania Aculeata in India on Long Term Basis - Subhash Chander; S C. Tripathi; Karnam Venkatesh; R. P. Meena; Neeraj Kumar; R. S. Chhokar; Nitesh Kumar; Shiv Ram Samota; Deepa Sharma; Gyanendra Singh (International Journal of Plant Production, 2023)

Performance evaluation of dimensionality reduction techniques on hyperspectral data for mineral exploration - Deepa C; Amba Shetty; Narasimhadhan A V (Earth Science Informatics, 2023)

Automated grading of diabetic retinopathy using CNN with hierarchical clustering of image patches by siamese network - V. Deepa; C. Sathish Kumar; Thomas Cherian (Physical and Engineering Sciences in Medicine, 2022)

Investigation of Kinetic Drug Release Characteristics and In Vitro Evaluation of Sustained-Release Matrix Tablets of a Selective COX-2 Inhibitor for Rheumatic Diseases - M. Karthikeyan; M. K. Deepa; E. Bassim; C. S. Rahna; K. R. Sree Raj (Journal of Pharmaceutical Innovation, 2021)

Single-Turnover Variable Chlorophyll Fluorescence as a Tool for Assessing Phytoplankton Photosynthesis and Primary Productivity: Opportunities, Caveats and Recommendations - Nina Schuback; Philippe D. Tortell; Ilana Berman-Frank; Douglas A. Campbell; Aurea Ciotti; Emilie Courtecuisse; Zachary K. Erickson; Tetsuichi Fujiki; Kimberly Halsey; Anna E. Hickman; Yannick Huot; Maxime Y. Gorbunov; et al. (Frontiers in Marine Science, 2021)
Phytoplankton photosynthetic physiology can be investigated through single-turnover variable chlorophyll fluorescence (ST-ChlF) approaches, which carry unique potential to autonomously collect data at high spatial and temporal resolution. Over the past decades, significant progress has been made in the development and application of ST-ChlF methods in aquatic ecosystems, and in the interpretation of the resulting observations. At the same time, however, an increasing number of sensor types, sampling protocols, and data processing algorithms have created confusion and uncertainty among potential users, with a growing divergence of practice among different research groups. In this review, we assist the existing and upcoming user community by providing an overview of current approaches and consensus recommendations for the use of ST-ChlF measurements to examine in-situ phytoplankton productivity and photo-physiology. We argue that a consistency of practice and adherence to basic operational and quality control standards is critical to ensuring data inter-comparability. Large datasets of inter-comparable and globally coherent ST-ChlF observations hold the potential to reveal large-scale patterns and trends in phytoplankton photo-physiology, photosynthetic rates and bottom-up controls on primary productivity. As such, they hold great potential to provide invaluable physiological observations on the scales relevant for the development and validation of ecosystem models and remote sensing algorithms.

The sea level variability and its projections over the Indo‐Pacific Ocean in CMIP5 models - J. S. Deepa; C. Gnanaseelan; Anant Parekh (Climate Dynamics, 2021)

Evaluation of oxidative stress in caprine anaplasmosis and effect of vitamin E–selenium in monitoring oxidative stress - G. Dhanasree; Usha Narayana Pillai; Chirayath Deepa; V. R. Ambily; M. Shynu; C. Sunanda (Tropical Animal Health and Production, 2020)

Complete Genome Sequence of Penicillium oxalicum Strain SGAir0226 Isolated from Outdoor Tropical Air in Singapore - Anjali Bansal Gupta; Nicolas E. Gaultier; Ngu War Aung; Rikky W. Purbojati; Elaine L. Oliveira; Anthony Wong; Deepa Panicker; Alexander Putra; Akira Uchida; Daniela I. Drautz-Moses; Stephan C. Schuster (Mycopathologia, 2020)

Multidecadal to decadal variability in the equatorial Indian Ocean subsurface temperature and the forcing mechanisms - Sandeep Mohapatra; C. Gnanaseelan; J. S. Deepa (Climate Dynamics, 2020)

Biases in the Tropical Indian Ocean subsurface temperature variability in a coupled model - Rashmi Kakatkar; C. Gnanaseelan; Jasti S. Chowdary; J. S. Deepa; Anant Parekh (Climate Dynamics, 2019)

The Tropical Indian Ocean decadal sea level response to the Pacific Decadal Oscillation forcing - J. S. Deepa; C. Gnanaseelan; Sandeep Mohapatra; J. S. Chowdary; A. Karmakar; Rashmi Kakatkar; Anant Parekh (Climate Dynamics, 2019)

Indole-3-carbinol improves neurobehavioral symptoms in a cerebral ischemic stroke model - Pankaj Paliwal; Gaurav Chauhan; Deepa Gautam; Debabrata Dash; Shashikant C. U. Patne; Sairam Krishnamurthy (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

The interannual sea level variability in the Indian Ocean as simulated by an Ocean General Circulation Model - J. S. Deepa; C. Gnanaseelan; R. Kakatkar; A. Parekh; J. S. Chowdary (International Journal of Climatology, 2018)
Limited coverage of tide gauge observations and limited length record of altimeter observations remain inadequate for the Indian Ocean sea level variability studies especially for longer periods. This study takes advantage of Ocean General Circulation Model (OGCM) simulations and ocean reanalysis to explore the interannual variability of sea level in the Indian Ocean. The model simulated sea level anomalies display good correlation with altimetry and reanalysis products. This consistency in model simulations with observations and reanalysis highlights the potential use of this OGCM in understanding the sea level variability. Analysis reveals that co‐occurrence years (years when Indian Ocean Dipole (IOD) and El Niño events co‐occur) contribute significantly towards the interannual variability in the Indian Ocean compared to pure IOD or El Niño events, and are characterized by persistent generation of open ocean downwelling, with maximum signals in the 10° to 5°S region. The OGCM experiments are carried out by modulating the forcing fields over the Pacific and the Indian Ocean to understand the physical mechanisms causing sea level variability. The experiments suggest that the remote forcing from the Pacific Ocean via Indonesian ThroughFlow (ITF) induce significant sea level changes in the southern Indian Ocean only with variability mostly in the decadal time scales and the northern and equatorial Indian Ocean are not affected by ITF. This study also shows that El Niño and IOD‐induced variations in zonal wind stress and wind stress curl mainly contribute the interannual sea level variations in the Indian Ocean. The forcing associated with the co‐occurrence years are multi‐phased with coastal and open ocean forcing. Whereas the pure IOD and El Nino forcing is mainly found only over the open ocean. The decadal variability in the ENSO is primarily responsible for the decadal sea level variability in the Indian Ocean by modulating ITF transport.

Indian summer monsoon rainfall variability during 2014 and 2015 and associated Indo-Pacific upper ocean temperature patterns - Rashmi Kakatkar; C. Gnanaseelan; J. S. Chowdary; Anant Parekh; J. S. Deepa (Theoretical and Applied Climatology, 2018)

The influence of diesel—truck exhaust particles on the kinetics of the atmospheric oxidation of dissolved sulfur dioxide by oxygen - Vimlesh Kumar Meena; Yogpal Dhayal; Deepa Saxena; Ashu Rani; C. P. Singh Chandel; K. S. Gupta (Environmental Science and Pollution Research, 2016)

Protocetraric acid: an excellent broad spectrum compound from the lichen Usnea albopunctata against medically important microbes - Kumar S. Nishanth; R.S. Sreerag; I. Deepa; C. Mohandas; Bala Nambisan (Natural Product Research, 2015)

Loss of P2Y2 Nucleotide Receptors Enhances Early Pathology in the TgCRND8 Mouse Model of Alzheimer's Disease - Deepa Ajit; Lucas T. Woods; Jean M. Camden; Christina N. Thebeau; Farid G. El-Sayed; Glen W. Greeson; Laurie Erb; Michael J. Petris; Douglas C. Miller; Grace Y. Sun; Gary A. Weisman (Molecular Neurobiology, 2014)

Multiresidue Analysis of Organochlorine Pesticides in Milk, Egg and Meat by GC–ECD and Confirmation by GC–MS - C. Selvi; M. Paramasivam; Deepa S. Rajathi; S. Chandrasekaran (Bulletin of Environmental Contamination and Toxicology, 2012)

A Model Study on Understanding the Influence of Arabian Sea Mini Warm Pool on Monsoon Onset Vortex Formation - R. Deepa; C. Gnanaseelan; M. Deshpande; P. S. Salvekar (Pure and Applied Geophysics, 2012)

Growth enhancement of black pepper (Piper nigrum) by a newly isolated Bacillus tequilensis NII-0943 - Syed G. Dastager; C. K. Deepa; Ashok Pandey (Biologia, 2011)

Paracoccus niistensis sp. nov., isolated from forest soil, India - Syed G. Dastager; C. K. Deepa; Wen-Jun Li; Shu-Kun Tang; Ashok Pandey (Antonie van Leeuwenhoek, 2011)

Potential plant growth-promoting activity of Serratia nematodiphila NII-0928 on black pepper (Piper nigrum L.) - Syed G. Dastager; C. K. Deepa; Ashok Pandey (World Journal of Microbiology and Biotechnology, 2011)

Plant growth-promoting activity in newly isolated Bacillus thioparus (NII-0902) from Western ghat forest, India - C. K. Deepa; Syed G. Dastager; Ashok Pandey (World Journal of Microbiology and Biotechnology, 2010)

On the relationship between Arabian Sea warm pool and formation of onset vortex over east-central Arabian Sea - R. Deepa; C. Gnanaseelan; P. Seetaramayya; S. G. Nagar (Meteorology and Atmospheric Physics, 2010)

Isolation and characterization of plant growth promoting bacteria from non-rhizospheric soil and their effect on cowpea (Vigna unguiculata (L.) Walp.) seedling growth - C. K. Deepa; Syed G. Dastager; Ashok Pandey (World Journal of Microbiology and Biotechnology, 2010)

Evidence for long‐term regional changes in precipitation on the East Coast Mountains in Mauritius - Deepa Senapathi; Fiona Underwood; Emily Black; Malcolm A. C. Nicoll; Ken Norris (International Journal of Climatology, 2010)
Global climate change and its impacts are being increasingly studied and precipitation trends are one of the measures of quantifying climate change especially in the tropics. This study uses daily rainfall data to determine if there are changes in the long‐term trends in rainfall variability in the East Coast Mountains of Mauritius during the last few decades, and to investigate the factors influencing the trends in the inter‐annual to inter‐decadal rainfall variability. Statistical modelling has been used to investigate the trends in total seasonal rainfall, the number of rain days and the mean amount of rain per rainy days and the local, regional and large‐scale factors that affect them on inter‐annual to inter‐decadal time scales. The strongest inter‐decadal trend was found in the number of rain days for both rainfall seasons, and the other variables were found to have weak or insignificant trends. Both local factors, such as the surrounding sea surface temperatures and large‐scale phenomena such as Indian Monsoon and the El Ni ñ o Southern Oscillation were found to influence rainfall patterns. Copyright © 2009 Royal Meteorological Society

Genome mapping of an apple scab, a powdery mildew and a woolly apple aphid resistance gene from open-pollinated Mildew Immune Selection - Vincent G. M. Bus; Heather C. M. Bassett; Deepa Bowatte; David Chagné; Chandra A. Ranatunga; Dulantha Ulluwishewa; Claudia Wiedow; Susan E. Gardiner (Tree Genetics & Genomes, 2010)

Characterization of plant growth-promoting rhizobacterium Exiguobacterium NII-0906 for its growth promotion of cowpea (Vigna unguiculata) - Syed G. Dastager; Deepa C. Kumaran; Ashok Pandey (Biologia, 2010)

Scientific evaluation of some Ayurvedic preparations for correction of iron deficiency and anemia - Dinesh C. Sharma; Deepa Chandiramani; Manminder Riyat; Praveen Sharma (Indian Journal of Clinical Biochemistry, 2007)

Structure of the extended diarrhea-inducing domain of rotavirus enterotoxigenic protein NSP4 - R. Deepa; C. Durga Rao; K. Suguna (Archives of Virology, 2007)

Phosphate starvation responses are mediated by sugar signaling in Arabidopsis - Athikkattuvalasu S. Karthikeyan; Deepa K. Varadarajan; Ajay Jain; Michael A. Held; Nicholas C. Carpita; Kashchandra G. Raghothama (Planta, 2007)

Copper Availability and Accumulation by Portulaca Oleracea Linn. Stem Cutting - R. Deepa; P. Senthilkumar; S. Sivakumar; P. Duraisamy; C. V. Subbhuraam (Environmental Monitoring and Assessment, 2006)